Prognostic value of HPV 16/18 genotyping and geminin mRNA quantification in low-grade cervical squamous intraepithelial lesion. Issue 2 (20th December 2021) - Zheng, Ziwen; Yang, Xiaorong; Yao, Xinyu; Li, Ling
ABSTRACT: Low-grade cervical squamous intraepithelial lesion is a precancerous neoplasia that has appreciable probability to evolve into malignancy. To explore the prognostic value of HPV 16/18 genotyping and geminin mRNA quantification in predicting the progressiveness of LSIL. We recruited 212 participants who were negative for intraepithelial lesion or malignancy (NILM 76), low-grade squamous intraepithelial lesion (LSIL 85), high-grade squamous intraepithelial lesion (HSIL 36) and cervical intraepithelial neoplasia grade cervical cancer grade 3, (CIN3 15) patients. Tissues were obtained during excisional treatment. HPV 16/18 genotyping and geminin mRNA qRT-PCR were performed. HPV 16/18 positivity rate and geminin mRNA level were integrated with the clinical parameters into a multivariate logistic model. Area under curve was yielded based on receiver operation curve derived from this multivariate logistic model. Follow-up visits were performed to LSIL patients with progression. HSIL patients have higher HPV 16/18 positivity rate and geminin mRNA levels than LSIL. Among HSIL, CIN3 have higher HPV 16/18 positivity rate and geminin mRNA levels. Multivariate logistic analysis showed that HPV 16/18 positivity and geminin mRNA expression status are independent factors for differentiating HSIL and LSIL. The baseline HPV 16/18 positivity rate and geminin mRNA levels of 18 LSIL patients who developed HSIL are significantly higher than non-progressive LSIL patients. The values examined at follow-up timepoints were also higher than baseline. These results suggest that geminin is implicated in the progression of LSIL and combining HPV 16/18 genotyping and geminin mRNA qRT-PCR could potentially differentiating the progressive LSIL and improve the efficacy of clinical intervention.